1986
DOI: 10.1246/bcsj.59.689
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis by Transition-Metal Carbides. VII. Kinetic and XPS Studies of the Decomposition of Methanol on TiC, TaC, Mo2C, WC, and W2C

Abstract: The catalytic decomposition of methanol was investigated on a series of powdered transition-metal carbides, such as TiC, TaC, Mo2C, WC, and W2C, which had been catalytically activated by evacuation at high temperatures. WC was found to produce methyl formate (HCOOCH3) with a high selectivity (above 80%), whereas CO and H2 were mainly produced on clean TaC, Mo2C, and W2C surfaces. XPS measurements combined with an analysis of the peak intensities revealed that the catalytic activation of WC and TaC was attribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Technologically, such materials have attracted attention as highly stable field electron emitters [2][3][4] and catalysts for various surface chemical reactions [5][6][7]. The metal compound TiN is one such material.…”
Section: Introductionmentioning
confidence: 99%
“…Technologically, such materials have attracted attention as highly stable field electron emitters [2][3][4] and catalysts for various surface chemical reactions [5][6][7]. The metal compound TiN is one such material.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that transition metal carbides have excellent catalytic activity in a wide variety of hydrogen-involved reactions [2][3][4][5][6][7][8][9][10][11], such as hydrocarbon synthesis from CO hydrogenation [3,[12][13][14][15], dehalogenation [8], hydrodesulfurization [16,17] and hydrodenitrogenation [18,19]. CH 4 dry reforming has received high attention, because it can convert these cheapest carbon containing materials into useful chemical products (CH 4 + CO 2 = 2CO + 2H 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Considerable attention has been focused in recent years on the chemical and physical properties of late transition metal carbides (TMC) because of their excellent catalytic properties that resemble group VIII metals in many hydrogeninvolved reactions [1][2][3][4][5][6][7][8][9]. In particular, they also have an interesting combination of useful properties such as extreme hardness, high melting point and metallic conductivity [10].…”
Section: Introductionmentioning
confidence: 99%